2018
DOI: 10.1111/pbi.12961
|View full text |Cite
|
Sign up to set email alerts
|

QQS orphan gene and its interactor NFYC4 reduce susceptibility to pathogens and pests

Abstract: Enhancing the nutritional quality and disease resistance of crops without sacrificing productivity is a key issue for developing varieties that are valuable to farmers and for simultaneously improving food security and sustainability. Expression of the Arabidopsis thaliana species-specific AtQQS (Qua-Quine Starch) orphan gene or its interactor, NF-YC4 (Nuclear Factor Y, subunit C4), has been shown to increase levels of leaf/seed protein without affecting the growth and yield of agronomic species. Here, we demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 64 publications
(129 reference statements)
1
48
0
Order By: Relevance
“…Both QQS and AtNF‐YC4 modulate carbon and nitrogen allocation, but the molecular mechanism by which the complex functions is still undetermined. Recently it was shown that overexpression of AtQQS and NF‐YC4 in Arabidopsis and soybean enhanced resistance/reduces susceptibility to viruses, bacteria, fungi, aphids and soybean cyst nematodes (Qi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Both QQS and AtNF‐YC4 modulate carbon and nitrogen allocation, but the molecular mechanism by which the complex functions is still undetermined. Recently it was shown that overexpression of AtQQS and NF‐YC4 in Arabidopsis and soybean enhanced resistance/reduces susceptibility to viruses, bacteria, fungi, aphids and soybean cyst nematodes (Qi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The canonical NF-Y is a heterotrimeric, eukaryotic transcription factor that is comprised of subunits NF-YA, NF-YB and NF-YC [31]. NF-Y has been associated with characteristics as diverse as cell division [32], cancer [33,34], drought tolerance [35], broad spectrum disease resistance [36], and carbon and nitrogen partitioning [37]. In animals and fungi, a single gene encodes each of the three NF-Y subunits.…”
Section: Resultsmentioning
confidence: 99%
“…The A. thaliana OG Qua Quine Starch ( QQS ) is known to regulate the primary metabolic functions of carbon and nitrogen partitioning, and affected protein content when it was overexpressed in soybean, maize, and rice 5 . An in-depth analysis showed that QQS and its interactor NF-YC4 could reduce Arabidopsis and soybean susceptibility to viruses, bacteria, fungi, aphids, and soybean cyst nematodes 6 . The salamander-specific protein Prod1 can regulate limb regeneration by determining the direction of limb growth 7 .…”
Section: Introductionmentioning
confidence: 99%